The Influence of Interpersonal Communication and Utilization of Information Technology Through the Quality of Public Services on Public Satisfaction at the Population and Civil Registry Service of West Tanjung Jabung Regency - Siska Diniati.Z; M. Zahari; Osrita Hapsara (Greenation International Journal of Economics and Accounting, 2025)
This study aims to describe interpersonal communication, technology utilization, public service quality, and public satisfaction, as well as to determine and analyze the influence of interpersonal communication and information technology utilization through public service quality on public satisfaction at the Population and Civil Registration Office of West Tanjung Jabung Regency. This type of research uses descriptive verification research. This study uses the PLS analysis method. The results of the study indicate that interpersonal communication, information technology, and public service quality play an important role in increasing public satisfaction at the Population and Civil Registration Office of West Tanjung Jabung Regency. Interpersonal communication has been proven to improve the quality of public services while encouraging increased public satisfaction. Likewise, the use of information technology contributes positively to strengthening service quality and has an impact on public satisfaction. In addition, the quality of public service itself has a strategic role as a factor that mediates the influence of interpersonal communication and information technology on public satisfaction, so it can be concluded that the better the communication, technology utilization, and service quality provided, the level of public satisfaction will also increase.